Absence of left circumflex coronary artery: case report and minireview - (:unkn) unknown (TERMEDIA PUBLISHING HOUSE LTD, 2012)
Absence of the left circumflex coronary artery (LCX) is a very rare coronary anomaly. The anomaly has been reported in only 0.003% of all patients who underwent routine coronary angiography. Although rare, the failure to visualize a coronary artery in its expected anatomical location might cause life-threatening complications such as total occlusion with acute coronary syndromes. In the present paper, we report a patient with absent LCX and discuss the previously reported cases in terms of diagnostic and clinical importance, association with atherosclerosis and other anomalies. We searched Medline (www.ncbi.nlm.nih.gov) for cases of absent LCX and found that so far absence of LCX has been reported 27 times and in 32 cases. Here in this case report and minireview we discuss the characteristics of the present case and previous 32 cases with absence of LCX. The majority of the patients were over 30 years old at the time of diagnosis and the condition is more common in females. Although absence of LCX is generally considered as a benign entity, it might be atherosclerotic and can cause acute coronary syndromes including myocardial infarction and be associated with other anomalies. Proper diagnosis of the absence of LCX is very important because it can be misinterpreted as a totally occluded LCX. In subjects with absent LCX, infarction in the superdominant RCA might be more dangerous. It is more common in females and although conventional coronary angiography is the most widely used diagnostic modality, multidetector computed tomography might also be helpful.
Keywords: absent; left circumflex coronary artery; INFERIOR MYOCARDIAL-INFARCTION; CONGENITAL ABSENCE; COMPUTED-TOMOGRAPHY; TERMINAL EXTENSION; DOMINANT COURSE; ANOMALIES; DISEASE